(untitled) (Medical Forum Monthly, 2024)
Objectives: To compare the infection rate in periumbilical incision and intraumbilical incision in laparoscopic appendectomy patients. Study Design: Randomized control trial study. Place and Duration of Study: This study was conducted at the Department of Surgery, NMC/NH, Multan from January 2016 to January 2017. Materials and Methods: A total of three hundred and ninety six patients enrolled in our trial and the patients were randomized in two equal groups (Group P and Group I). Data collected was entered in computer program SPSS version 23 and analyzed. Mean ± standard deviation were calculated for numerical values like infection score. Categorical variables were presented as frequencies and percentages. Effect modifier like age and gender were controlled by stratification of data. Post stratification chi square test was applied. A p value ≤ 0.05 was considered statistically significant. Results: Group P treated with periumbilical incision and Group I treated with intraumbilical incision. It was seen that in group P, 3.5% (n=7) patients were having wound infection while 96.5% (n=191) were not, and in group I, only 1.5% (n=3) were having wound infection while 98.5% (390) were not. Conclusion: The ratio of complication in intraumlical incision is less than periumbilical incisions. So the incision on intraumbilical region is easy and safe to replace the surgery of incision on periumbilical region with best cosmetic results.